The operating development of sub-district health management by community participation: Nong Wang Sub-district, Nikhom Kham Soi District, Mukdahan Province - Premsing, Warunee; Wongkongdech, Adisorn; Wongkongdech, Ranee (UBRU Journal for Public Health Research, 2019)
The development for sub-district health management by community participation: Nong wang sub-district, Nikhom Kham Soi District, Mukdahan province. The research (Action research) and technical applications. Creating and using Strategic Route Map (SRM) with the process. Workshop The community leaders who participated in the research. Purposely To study the situation in the context of education models and development processes. And Key Success Factors Process Improvement District manages the public health Nong wang sub-district, Nikhom Kham Soi District, Mukdahan province. The results showed that the level of knowledge about operation management district health before and after the operation showed that the level of knowledge before and after. The operation was significantly different (t =, 14.33 P < 0.05). The participation management district overall health, found that the participation level overall at a high level (Mean. 3.72 SD =, 0.11) model of the operational model management district public health Nong Wang Sub-district, Nikhom Kham Soi, Mukdahan Province consists of 7 steps to solve the problem and the community context (S = Study) measured before operation (E = Evaluation) plan. Implementation using strategic route map (S = SRM) follow the action plan (O = Operating) conference track operation results. F = Follow up) administered after operation (R = Results) and conclusion and take off performance lessons (S = Summary) suggestion in research. The level of participation in planning. The level of participation is minimal. It should take measures so that community members. Awareness and to contribute to sustainability. The research involved. The research was carried out in line with the needs of the target audience. The development features vocal understanding the behavior of individuals who want to showcase their talent. As an example to others introducing others, makes the audience with enthusiasm, remember to seek knowledge to apply. These strategies can be applied in other areas via the club in the district and organizations, which there are meeting to exchange the ideas.